Knowledge levels of midwives regarding the interpretation of cardiotocographs at labour units in KwaZulu-Natal public hospitals - Sindiwe James; Ntsepiseng E. Maduna; David G. Morton (AOSIS, 2019)
Background: The primary purpose of cardiotocography is to detect early signs of intrapartum hypoxia and improve foetal outcomes. Intrapartum hypoxia remains the major cause of perinatal deaths during monitored labours. This is attributed to the midwives' lack of knowledge and skills in the foetal implementation and interpretation of cardiotocographs. Objectives: This study aimed to establish midwives' knowledge and interpretive skills of cardiotocography. Method: The study employed a quantitative research approach with an explorative, descriptive, cross-sectional design. A total of 226 purposively selected participants were asked to complete a self-administered, structured questionnaire, of which 125 responded by completing the questionnaire. The study was conducted in labour wards in KwaZulu-Natal public hospitals in 2014. Data analysis was performed by means of descriptive and inferential statistics using analysis of variance. Results: The findings revealed that the midwives in KwaZulu-Natal public hospitals were found to be clinically lacking in knowledge of cardiotocography. Conclusion: The limited cardiotocographic knowledge of the midwives in KwaZulu-Natal public hospitals was possibly because of a lack of in-service training, as more than half of the participants (70%) indicated a need for this.